Comparative study of electrocardiographic alterations, heart rate and arterial blood pressure between seropositives and seronegatives for Trypanosoma cruzi in valley of Vítor, Arequipa-Perú - Sánchez Sánchez, Y. (2024)
Introduction: the cardiac syndrome is the main cause of morbidty and mortality in Chagas disease, and its pathogenesis appears to be related to abnormalities of the autonomous nervous system which affect cardiovascular physiology. Objectives: to compare the values of heart rate ,blood pressure and electrocardiographic (EKG) abnormalities of the infected population with those of the control population. Materials and Methods: this is an analytic, observational, cross sectional study made in the valley of Vítor, Arequipa, from 2004 to 2005. Volunteers over 15 yearse of age ere studied: 25 T. cruzi seropositive an 50 T. cruzi seronegative persons. Examinations including heart rate, blood pressure and standard 12-lead EDGs were performed, comparing the results between the groups. Results: heart rate and blood pressure values were similar between seropositive subjects and their controls; the same was true of sinus bradycardia, hypotension and hypertension. EKG abnormalities were found in 40% of seropositives and 26% of the controls; the difference didnt reach statistical significance. The EKG abnormalities detected most often in the 2 groups were nonspecific repolarization changes, sinus bradycardia, left anterior bundle block, and supraventricular estrasystoles. Complete right bundle block and partial left anterior bundle block were seen in seropositive persons under 40. Conclusions: the prevalence of cardiovascular abnormalities was similar between subjects infected with T. cruzi and their controls. The EKG abnormalities seen most frequently are different from those typically described in Chagas disease patients.